A TEI Customization for Paper and Watermarks Descriptions. Issue 1 (11th December 2020) - Müller, Ermenegilda
Abstract : Watermarks are key to retracing the origins of paper manuscripts and early printed books and to understanding the context in which they were produced. TEI-P5, one of the most commonly used XML standards for digital descriptions of text-bearing objects, offers the possibility to describe watermarks, but not yet in a sufficiently detailed and consistent manner. The present article introduces a TEI-P5 customization for the description of paper and watermarks based on the International Standard for the Description of Paper, Watermarks and Paper Moulds in Relational Databases (IPHN 2.1.1). This customization provides TEI users with tools to make detailed, structured and standardized descriptions of paper, watermarks, and paper moulds. Such descriptions have the potential to improve the communication and collaboration between the different scholars working on paper manuscripts and early printed books. Moreover, once organized into a database, they can be mined in order to determine the origin and circulation of paper types. Therefore, the present customization can represent a strong asset in the study of the origins and material contexts of paper documents, handwritten or printed.